2022
DOI: 10.3389/fpsyg.2022.849489
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Emotional Well-Being, and Perceived Faculty Incivility and Just Behavior Before and During COVID-19

Abstract: This research set out to measure the impact of the lockdown condition and social distancing imposed on higher education by the Israeli government during the COVID-19 period and the shift to online learning, on students’ emotional well-being, the way they perceived their teachers’ just behavior, and faculty incivility, compared to pre-pandemic conditions. An additional aim was to explore the set of connections among these factors. The total sample included 396 undergraduate students from three academic colleges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…The impact of social distancing on mental stress in researchers and students was not surprising, as many other surveys had reported similar conditions in different populations (Alessi et al, 2021;Alt et al, 2022;Cao et al, 2020;Dong et al, 2022). The personal experience and observation of the authors indicated that social distancing indeed had led to the distancing of researchers and reduced social interactions between researchers.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The impact of social distancing on mental stress in researchers and students was not surprising, as many other surveys had reported similar conditions in different populations (Alessi et al, 2021;Alt et al, 2022;Cao et al, 2020;Dong et al, 2022). The personal experience and observation of the authors indicated that social distancing indeed had led to the distancing of researchers and reduced social interactions between researchers.…”
Section: Discussionmentioning
confidence: 66%
“…Administrative matters were also often delayed when fewer administrative staff worked in the office. The unavailability of staff has been reported to be associated with perceived incivility of faculty by students (Alt et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This pandemic resulted in a certain shift in the educational environment with the majority of teachers and students having no or very little experience of OLE and facing difficulty in developing the teaching and learning process 17,18 . One of the reasons for disruptive behavior can be the challenges faced by both faculty and students to accustom to the new learning environment 19 . Multiple studies have reported the prevalence of incivility along with strategies to prevent this in face‐to‐face learning 2,3,5,20–22 .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 One of the reasons for disruptive behavior can be the challenges faced by both faculty and students to accustom to the new learning environment. 19 Multiple studies have reported the prevalence of incivility along with strategies to prevent this in face-to-face learning. 2,3,5,[20][21][22] To our knowledge no study has been carried out to assess the prevalence, and characteristics of IOLE from dental students and faculty perceptive.…”
Section: Introductionmentioning
confidence: 99%